Efficiency and productivity of manufacturing sector in Malaysia - Zakaria, Nurhidayah (2021)
The substantial increment of gross domestic product (GDP) of the manufacturing sector from year to year and its contribution to the Malaysian economy is the evidence of the relevance for this sector to the impetus of the Malaysian economy. As it is known, efficiency and productivity growth are essential elements to guarantee that a sector is sustainable over the long haul. However, from 2006 until 2013, starting with the sixth Malaysian Plan (MP), labour productivity for Malaysia’s manufacturing sector showed a weak growth compared to the other major sectors. The hindrances were due to the fragmentation of labour productivity, which is the capital intensity and total factor of productivity. The study took a sample panel data from 1990 until 2015, where it started from the Sixth MP as it was a big stage for Malaysia to maintain the momentum of rapid economic growth. To identify the factors that influence labour productivity, the Pooled Mean Group (PMG) panel data estimation technique was executed. The study found that variables-wage and consumer price index are positively significant to labour productivity in the sector. However, a similar analysis was also performed for each state, and the outcome was varied. Subsequently, to develop and increase the production of this sector, the degree of efficiency and productivity change by manufacturing sector in each state in Malaysia was measured by using Data Envelopment Analysis (DEA) and Malmquist Productivity Index (DEA-MPI) method. Based on the result of DEA, it is found that Selangor has genuinely achieved the 100% of technical efficiency score, and became the benchmark for the rest of inefficient states. Also, factors determining the level of technical efficiency have been analysed, and the outcomes indicated that investment and workers with primary education attainment are significant. The study was also done at each state level, and the findings are verity, wherein variables of interest affect various states. Lastly, through DEA-MPI, almost all states experienced productivity growth. On a national scale over the period of research, Malaysia’s manufacturing sector has experienced a productivity growth of 2.3%, with technological change as a dominant source of the productivity with 5%. An analysis to identify the influencing factors that affect the productivity change was conducted. At a national level, the result showed that only net capital and workers with primary education attainment were significant. Nevertheless, at the state level, all variables were significant in different states. The manufacturing industries have consistently played a significant role in Malaysia in the context of competitiveness in order to promote its growth and economic development. The expanding cognizance in regards to the efficiencies and productivity of the manufacturing sector is the crucial element of feasible and long-term growth. Simultaneously, it was noticed that top to bottom research at the state level is likewise significant as a subject to scrutiny. The empirical estimates of the Malaysian manufacturing’s efficiencies and productivities performances point to the fact that more considerable enhancement in terms of inputs is required. Based on this study, the policymakers, manufacturers, and workers are called for in order to be always well informed and play a role in endeavours to improve the high efficiency and productivity for the sector.